2023
DOI: 10.1021/acscatal.3c01412
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Robust and Highly Active PCP Cobalt(II) Catalyst for Linear-Selective Hydroboration of Terminal and Internal Olefins

Abstract: We report the design and synthesis of cobalt complexes of L 2 X-type ligands for olefin hydroboration guided by the consideration of catalyst stability. Among the series of PCPligated Co(II) and Co(III) pincer complexes, the complex with iPr phosphino substituents exhibits broad scope, high functional group tolerance, and high catalytic activity at ppm catalyst loadings (17 ppm, 0.001 mol %) in the hydroboration of terminal olefins with pinacolborane (HBpin), furnishing anti-Markovnikov addition products. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In addition, our study demonstrates that both [PSiP] pincer Co­(I) and Co­(III) complexes exhibit good catalytic activity for alkene hydrosilylation reactions. , Previous work has shown that Co­(II) complexes also have good to excellent catalytic activity for alkene hydrosilylation reactions. Based on the above research, as a continuation of our work on the [PSiP] pincer cobalt system, this article explores the catalytic effect of [PSiP] pincer Co­(II) complexes on the alkene hydrosilylation reaction.…”
Section: Introductionmentioning
confidence: 66%
“…In addition, our study demonstrates that both [PSiP] pincer Co­(I) and Co­(III) complexes exhibit good catalytic activity for alkene hydrosilylation reactions. , Previous work has shown that Co­(II) complexes also have good to excellent catalytic activity for alkene hydrosilylation reactions. Based on the above research, as a continuation of our work on the [PSiP] pincer cobalt system, this article explores the catalytic effect of [PSiP] pincer Co­(II) complexes on the alkene hydrosilylation reaction.…”
Section: Introductionmentioning
confidence: 66%
“…Among many well-defined earth-abundant metal catalysts for alkene hydroboration that have emerged over the past decade, cobalt catalysts turned out to be most attractive with respect to the ligand versatility, good regioselectivity of products and high TOFs. 8–13 Numerous cobalt catalyst systems have been reported for either branched (Markovnikov) or linear (anti-Markovnikov) selectivity by Chirik, 9 Lu, 10 Thomas, 11 Huang, 12 Findlater 13 and our group, 8 respectively. While all cobalt-based discrete molecular catalysts reported thus far realized alkene hydroboration with relatively low TOFs (<300 h −1 ), we have disclosed that a one-dimensional Co II -coordination polymer assembled from a divergent ligand, 4′-pyridyl-2,2′; 6′,2′′-terpyridine (pytpy), enabled Markovnikov-selective hydroboration of aryl alkenes with high TOFs up to 47 520 h −1 .…”
Section: Introductionmentioning
confidence: 88%
“…Liu, Huang, and co-workers reported the use of a pincer-ligated cobalt as an especially efficient linear-selective hydroboration catalyst . This catalyst provides consistently high yields, often above 95%, with very low catalyst loadings (0.02 mol %), demonstrating turnover numbers of up to 90,000 (Scheme ).…”
Section: Recent Reports On Co-catalyzed Reactionsmentioning
confidence: 99%